Analisis Kohesi Wacana Naratif “Mendongeng Lima Menit” pada Tabloid Tokoh - Sri Kusuma Wardani, Wayan; Suparwa, I Nyoman (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p12, 2018)
This study entitled “Analisis Kohesi Wacana Naratif ‘Mendongeng Lima Menit’ pada Tabloid Tokoh”. The aims of this study are (1) to identify the lexical cohesive device, (2) to identify the grammatical cohesive device, and (3) to identify the cohesiveness degree of a narrative discourse in “Mendongeng Lima Menit” on Tokoh tabloids. The method used in collecting the data in this study is observation method, and then the data were analyzed with descriptive qualitative method, quantitative method, and distributional method. The method used in presenting the data analysis are formal and informal methods. The source of data in this study is taken from the narrative discourse of “Mendongeng Lima Menit” in Tokoh tabloids, which consists of 27 fairytale stories. This study used the theory of cohesion by Halliday & R. Hassan in their book Cohesion in English (1976:4). This study found types of lexical cohesion, grammatical cohesion, and the cohesiveness degree in the narrative discourse “Mendongeng Lima Menit” on the tabloids of Tokoh. The lexical cohesion found were synonym, antonym, repetition, colocation, and equivalency. The grammatical cohesion found were reference, substitution, ellipsis, and conjunction. The cohesiveness degree of the narrative discourse “Mendongeng Lima Menit’ was high, which was 92,7% and they were built by 930 cohesive devices. The grammatical cohesion included the 210 references (22,6%), 44 substitutions (4,7%), 12 ellipsis (1,3%), and 528 conjunctions (56,8%). The lexical cohesion included 6 synonyms (0,64%), 31 antonyms (3,3%), 57 repetitions (6,1%), 36 colocations (3,9%), and 6 equivalencies (0,64%).